Access to vaccine information and recommendation practice of non-EPI vaccines among vaccination service providers in China - Qian WANG; Kai-yi HAN; Shi-yi TU (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To investigate the access to vaccine information and recommendation practice of non-Expanded Programme on Immunization (EPI) vaccines among vaccination service providers (VSPs) in China and to provide suggestions on promoting recommendation intention of non-EPI vaccines among VSPs. Methods A cross-sectional online survey was conducted among 584 VSPs recruited using two-stage cluster sampling in Anhui and Shaanxi province and Shenzhen municipality in central, western, and eastern China during January 2019. The participants' information on socio-demographic characteristics, recommendation practice of non-EPI vaccines, channels and sources for getting knowledge about vaccination were collected with a self-administered questionnaire. Univariate chi-square test and multivariate logistic regression model were adopted in data analyses. Results Of the 555 participants with valid responses, only 51.53% reported frequent recommendation of non-EPI vaccines to clinic attendees. Among the participants, 83.60%, 61.08%, 36.64%, and 58.92% reported getting information on non-EPI vaccines from training programmes/seminars, medical workers, professional books, and media and the proportions of the participants getting the information disseminated by Chinese Center for Disease Control and Prevention (CDC), vaccine manufacturers, and government agencies were 97.48%, 31.17%, and 29.73%, respectively. The results of multivariate logistic regression analysis indicated that the participants working in Shenzhen municipality (odds ratio [OR] = 0.66, 95% confidence interval [95% CI]: 0.51 - 0.85), being nurses (OR = 0.65, 95% CI: 0.46 - 0.92) were less likely to carry on recommendation of non-EPI vaccines; while, the participants aged over 45 years (OR = 2.04, 95% CI: 1.01 - 4.11), getting non-EPI vaccine-related information from training programmes/seminars (OR = 2.11, 95% CI: 1.62 - 2.76)/professional books (OR = 1.28, 95% CI: 1.08 - 1.51) and disseminated by vaccine manufacturers (OR = 1.55, 95% CI: 1.11 - 2.18) were more likely to recommend non-EPI vaccines to clinic attendees. Conclusion The practice of recommendation on non-EPI vaccines among VSPs is at a low level in China. The results of the study suggest that effective measures such as promoting dissemination of non-EPI vaccine-related information in training programmes/seminars and professional books should be implemented to increase the VSPs' recommendation practice.